European Agricultural Policy: Is there really no alternative? - Eckart Guth (Intereconomics, 1985)
In the intense political debate on the reform of the Common Agricultural Policy there is a high degree of consensus that the present rates of production growth must be stopped and structural surpluses dismantled. On the other hand, there is broad agreement that the structural adjustment of agriculture must not lead to unacceptable social hardships. Is an alternative to the present CAP which meets these criteria conceivable?
Keywords: 330; Ec